Efectos de extractos vegetales en pulgón (Myzus persicae) en el cultivo de lechuga (Lactuca sativa) en condiciones controladas - Gavilanes Pillajo, Johana Paola (2024)
The aphid is a crucial pest because it causes direct damage to crops, and its presence reduces the quality of the commercial product. This research was carried out at the Technical University of Cotopaxi and its objective was to evaluate the effect of plant extracts on the control of Myzus persicae on Lactuca sativa lettuce under controlled cultivation conditions at three concentrations 0%, 25% and 50%, arranged in a completely randomized design with 9 treatments and 2 replicates, In each treatment, the infestation of 20 individuals was carried out at the beginning on the leaves of the plants to be evaluated and the same environmental conditions were provided to favor the permanence of these during the entire experimental phase, for the application it was done with an atomizer in each experimental unit. Mortality data was taken every 10 minutes for forty minutes where the dead individuals were counted and extracted from each of the treatments. From the data obtained it was determined that the extracts evaluated did control Myzus persicae, with an average of 19.5 dead individuals per rue (Ruta graveolens) at 50% concentration, followed by (Anethum graveolens) with 50% concentration with an average of 19 dead individuals while (Nicotiana glauca) presented an average of 14.5 dead individuals.